2001
DOI: 10.1159/000045958
|View full text |Cite
|
Sign up to set email alerts
|

Onset, Time Course, and Persistence of Increased Haemodialysis-Induced Breath Isoprene Emission

Abstract: Recent findings of increased isoprene emission in the exhaled breath of patients undergoing haemodialysis and experimental evidence of the potential toxic and cancerogenic effects of isoprene hydrocarbon led us to assess how long haemodialysis patients are exposed to how much isoprene after a single haemodialysis session. Patients with end-stage renal failure on regular 4-hour (from 08.00 to 12.00 h) maintenance haemodialysis three times weekly were monitored. The breath isoprene content was analyzed by gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…This characteristic breath isoprene behavior in response to dialysis has already been reported by numerous investigators [18-29], however, this is the first time that it is confirmed by parallel blood measurements. The advanced explanations for this phenomenon include hemodynamic stress, fluctuations of respiratory variables, or activation of metabolic pathways leading to mevalonic acid synthesis [19,21-23], nevertheless, none of them seems to be adequate [18]. Isoprene has received a growing interest in the field of breath gas analysis due to the fact that it may serve as a sensitive, non-invasive indicator of several diseases in human organism [31].…”
Section: Resultsmentioning
confidence: 99%
“…This characteristic breath isoprene behavior in response to dialysis has already been reported by numerous investigators [18-29], however, this is the first time that it is confirmed by parallel blood measurements. The advanced explanations for this phenomenon include hemodynamic stress, fluctuations of respiratory variables, or activation of metabolic pathways leading to mevalonic acid synthesis [19,21-23], nevertheless, none of them seems to be adequate [18]. Isoprene has received a growing interest in the field of breath gas analysis due to the fact that it may serve as a sensitive, non-invasive indicator of several diseases in human organism [31].…”
Section: Resultsmentioning
confidence: 99%
“…Increased concentration of isoprene has been reported in breath after smoking [109]. Several studies found elevated isoprene breath concentrations during and after hemodialysis [110]. Relatively higher concentrations of sulfur-containing compounds have been reported in liver transplant patients [111] and patients with liver disease [112].…”
Section: Underlying Principle In Exhaled Breath Analysismentioning
confidence: 99%
“…Davies et al reported that isoprene concentration is significantly higher for patients on hemodialysis than for normal controls [131]. Also, as measured by SIFT-MS, breath isoprene level was markedly elevated immediately after treatment, as confirmed by Trovarelli et al [135]. Capodicasa et al found that isoprene levels were increased in exhaled air during hemodialysis, although they did not find any change in the exhaled concentrations of alkanes [136].…”
Section: Perspective | Calenic and Amannmentioning
confidence: 85%